Effects of Surface Functionalization of Lignin on Synthesis and Properties of Rigid Bio-Based Polyurethanes Foams - Zhang, Xuefeng (Polymers (Basel), 2018)
We report the preparation of lignin-based rigid polyurethane (RPU) foams from surface functionalized kraft lignin via a simple and environmentally benign process. Lignin was functionalized with polyisocyanate at 80 °C for 1 h, the resulting lignin-polyisocyanate prepolymer was confirmed by increased viscosity and Fourier-transform infrared spectroscopy (FTIR). The RPU foams containing up to 30% surface functionalized lignin as a substitute for petroleum-based polyols exhibited comparable thermal and mechanical properties to conventional RPU foams. The lignin-based RPU foams prepared from surface functionalization outperformed RPU foams without the surface functionalization, showing up to 47% and 45% higher specific compressive strength and modulus, respectively, with a 40% lignin substitution ratio. Thermal insulation and temperature-stability of the two types of the foams were comparable. The results indicate that the surface functionalization of lignin increases reactivity and homogeneity of the lignin as a building block in RPU foams. The life cycle assessment for the lignin-based RPU foams shows that the surface functionalization process would have overall lesser environmental impacts when compared with the traditional manufacturing of RPU foams with synthetic polyols. These findings suggest the potential use of surface functionalized lignin as a sustainable core material replacement for synthetic polyols in building materials.